FROM RISK TO OPPORTUNITY: STRATEGIES FOR PROFITABLE AND RESILIENT INFRASTRUCTURE IN HAZARD-PRONE KASHMIR VALLEY, INDIA - Asif Bashir; Naseer Ahmad Bhat; Amir Arshid; Shagufta Mohi ud din; Muskan Nazir; Amir Wani (PT. Radja Intercontinental Publishing, 2025)
Infrastructure development in geologically unstable regions demands an integrated approach that harmonizes engineering resilience with economic viability. This study critically examines the vulnerabilities posed by earthquakes, landslides, and soil instability in the Kashmir Valley, emphasizing their ramifications on infrastructure investment. By leveraging geotechnical risk assessments, structural vulnerability analyses, and economic modeling, the research delineates pathways for sustainable and profitable infrastructure development in hazard-prone zones. Through empirical case studies and global best practices, the study underscores the efficacy of innovative construction methodologies such as seismic retrofitting, base isolation, and bioengineering solutions for slope stabilization. Additionally, the financial dimension is scrutinized through cost-benefit analyses, which reveal the long-term fiscal prudence of investing in resilient infrastructure, mitigating potential economic losses. Policy frameworks, including risk-informed zoning regulations and incentivized public-private partnerships, are examined to foster risk-adjusted investment strategies. The findings advocate for a paradigm shift wherein geological risks are repositioned as opportunities for pioneering robust, disaster-resistant infrastructure that aligns with sustainability imperatives. The study’s recommendations serve as a pathway for policymakers, engineers, and investors seeking to fortify infrastructure against natural hazards while ensuring economic feasibility.